The Role of Intrinsic and Extrinsic Quality Attributes of Makassar Traditional Food as a Culinary Tourism Attraction - Amirullah, Amirullah (Journal of Management and Administration Provision, 2025)
The interest in the growth of culinary tourism in Makassar City, which has a lot of potential, is the foundation of this study. Analyzing how people perceive the quality of traditional food products is the aim of this study. Specifically, we look at how people perceive the quality of intrinsic attributes (like color, taste, smell, and appearance) and extrinsic attributes (like brand, denomination of origin, and image of traditional products) in relation to the most popular government-provided tourist attractions. However, there is still a lack of promotion of traditional food on government tourism sites. These are the justifications for conducting this investigation. Tourists who visited the culinary icon via random sample served as the study's subjects. The questionnaire approach was used to obtain data. Additionally, research data collected via documentation and questionnaires was examined, coded, validated, and tabulated for analysis. The study's findings suggest that both internal and extrinsic quality have an impact on culinary tourism visits. Makassar City's traditional cuisine can satisfy the requirements that are categorized into menu items that can be served as drinks, appetizers, main dishes, and desserts.